A Location Predicting Method for Indoor Mobile Target Localization in Wireless Sensor Networks. (20th March 2013) - Gao, Peng; Shi, Weiren; Zhou, Wei; Li, Hongbing; Wang, Xiaogang
Abstract : Node position information is one of the important issues in many wireless sensor networks' usages. In this paper, based on path planning, a location predicting method (PPLP) for indoor mobile target localization is proposed. We first establish the path planning model to constrain the movement trajectory of the mobile target in indoor environment according to indoor architectural pattern. Then, one certain localization result can be obtained using MLE algorithm. After that, based on the path-planning model and some previous localization results, the most likely position of the target in the next time interval can be predicted with the proposed predicting approach. Finally, the MLE result and prediction result are weighted to obtain the final position. The simulation results demonstrate the effectiveness of the proposed algorithm.